PENERAPAN STRATEGI PEMBELAJARAN KREATIF PRODUKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI OPTIK - Bambang Suprayogi (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2015)
Based on preliminary observations conducted in class VIII SMP Negeri 1 Nganjuk 2013/2014 school year it was found some learning problems in Natural Sciences (Physics), they are: the students in the class were passive, less interested in learning, the task result of the students’ assignment were low, and the students wanted to learn if they only have a homework. This is why the results of students’ learning achievement obtained is very low. Students will be forced to study if they have a test or assignment. The problems solved by using creative-productive learning strategies. Learning strategy is believed to nurture, enable and empower students' thinking skills. The design of the study in this research is a class act. Subjects were students VIII.6 grade school year 2013/2014, amounting to 30 people consisting of 12 male students and 18 female students. Data collected using observation, daily tests and questionnaires. Data processing was performed by descriptive qualitative based on the data collected. Based on the research that has been done, it can be concluded that "student learning outcomes are achieved, showing a percentage increase of 16.67%. The average score obtained by the students showed an increase of 5.1. "This study supports the results of research Alazmi (2010) which states that productive creative learning strategies can improve students’ learning outcomes VIII.B class of MTs Diniyah Putri Pekanbaru 2009/2010 on subject of lines on a triangle. KEYWORD: productive creative learning strategies, student learning outcomes